The Response of Volvariella volvacea to Low-Temperature Stress Based on Metabonomics - Zhao, Xu; Chen, Mingjie; Li, Zhiping; Zhao, Yan; Yang, Huanling; Zha, Lei; Yu, Changxia; Wu, Yuejin; Song, Xiaoxia (Frontiers in Microbiology, 2020)
Low temperature can lead to the autolysis of Volvariella volvacea, hindering its growth and preservation and severely reducing its yield and quality. This autolysis of V. volvacea at low temperature has been reported, but a metabolomics-based investigation of the underlying mechanisms of the V. volvacea response to low temperature has not been reported. Therefore, this study aimed to explore the changes, levels and expression patterns of V. volvacea metabolites at low temperature. To understand the metabolic differences within V. volvacea, two strains with different levels of low-temperature tolerance were treated in an ice bath at 0 ℃ for 2, 4, 8, and 10 h, while the blank control group was treated for 0 h. Metabonomics analysis was adopted to study the changes in V. volvacea in response to low temperature and the differences between the two different strains. Metabolic curves were analyzed at different time points by high-performance liquid chromatography-mass spectrometry (HPLC-MS). A total of 216 differential metabolites were identified and enriched in 39 metabolic pathways, mainly involving amino acid metabolism, carbohydrate metabolism, the TCA cycle, energy metabolism, etc. In this paper, we report the metabonomic analysis of V. volvacea in response to low temperature and compare the differences in metabolite expression between the low-temperature-resistant strain VH3 and the low-temperature-sensitive strain V23. Finally, the putative low-temperature resistance mechanism of VH3 is revealed at the metabolic level. This study provides a theoretical basis for revealing the regulatory mechanism of low-temperature resistance in V. volvacea and for future molecular breeding efforts.